An investigation into the effect of climate change on eutrophication and surface water quality of Voelvlei Dam with an emphasis on algal growth - Ally, Sayed Hanief (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.